2018
DOI: 10.1097/lbr.0000000000000454
|View full text |Cite
|
Sign up to set email alerts
|

Combined Endosonography Reduces Time to Diagnose Pulmonary Coccidioidomycosis

Abstract: Coccidioidomycosis causes significant morbidity in endemic areas. In the absence of sensitive diagnostic serologic testing, clinicians have increasingly relied on lung and lymph node biopsies for diagnosis. Recently, endobronchial ultrasound guided transbronchial needle aspiration (EBUS-TBNA) has been shown to be an excellent sampling method for the diagnosis and staging of lung cancers, especially when combined with endoscopic ultrasound guided fine needle aspiration (EUS-FNA). We present 13 consecutive cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…EBUS was also found to be effective in the diagnosis of pulmonary mucormycosis in a debilitated patient who was not fit enough to undergo invasive procedures [33]. The use of EBUS also facilitates rapid diagnosis in patients with other endemic fungal infections such as coccidioidomycosis [34].…”
Section: Main Textmentioning
confidence: 99%
“…EBUS was also found to be effective in the diagnosis of pulmonary mucormycosis in a debilitated patient who was not fit enough to undergo invasive procedures [33]. The use of EBUS also facilitates rapid diagnosis in patients with other endemic fungal infections such as coccidioidomycosis [34].…”
Section: Main Textmentioning
confidence: 99%
“…No complications were noted in the study. The study concluded that combined endosonography facilitated early and accurate diagnosis of pulmonary coccidioidomycosis (67).…”
Section: Role Of Combined Ebus/eus In Diagnosis Of Granulomas and Infectionsmentioning
confidence: 94%
“…46 In one study, combined EBUS/EUS was diagnostic for pulmonary coccidiomycosis in 89% of sampled patients and the mean time to diagnosis was shorter (1.6 days) than with BAL (6.3 days). 47…”
Section: Endosonography In Lymphoma Granulomatosis and Mediastinal Cystsmentioning
confidence: 99%